2003
DOI: 10.1095/biolreprod.102.007088
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid-Permeable Anion Channels in Early Mouse Embryos and Their Possible Effects on Cleavage1

Abstract: Effects of several Cl(-) channel blockers on ionic currents in mouse embryos were studied using whole-cell patch-clamp and microelectrode methods. Microelectrode measurements showed that the resting membrane potential of early embryonic cells (1-cell stage) was -23 mV and that reduction of extracellular Cl(-) concentration depolarized the membrane, suggesting that Cl(-) conductance is a major contributor for establishing the resting membrane potential. Membrane currents recorded by whole-cell voltage clamp sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
(31 reference statements)
2
11
0
Order By: Relevance
“…In the 1-, 4-, and 8-cell stages, the DIDS-sensitive current constituted all the Cl K -sensitive current. The electrophysiological characteristics of this outwardly rectifying Cl K current were similar to that of a current described previously in the preimplantation mouse embryo under both isotonic and hypotonic conditions (Kolajova & Baltz 1999, Kolajova et al 2001, Sonoda et al 2003. In the blastocyst, this DIDS-sensitive current was present in both the TE and the ICM.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In the 1-, 4-, and 8-cell stages, the DIDS-sensitive current constituted all the Cl K -sensitive current. The electrophysiological characteristics of this outwardly rectifying Cl K current were similar to that of a current described previously in the preimplantation mouse embryo under both isotonic and hypotonic conditions (Kolajova & Baltz 1999, Kolajova et al 2001, Sonoda et al 2003. In the blastocyst, this DIDS-sensitive current was present in both the TE and the ICM.…”
Section: Discussionsupporting
confidence: 84%
“…mRNAs encoding all the Clcn channels were detected throughout development extending a previous report of Clcn expression in zygotes (Sonoda et al 2003). Two types of ClC activities were detected using whole-cell voltage clamp methods.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Anion channels, such as Cl -channels, play several roles, but the main role is the regulation of cell volume in somatic cells and in early preimplantation embryos. During embryo culture, the uptake of amino acids was shown to be mediated by Cl -channels in the mouse (Sonoda et al, 2003), and swelling-activated anion current in early mouse embryos was shown to be developmentally regulated and cell-cycle dependent (Kolajova et al, 2001).…”
Section: Mammalsmentioning
confidence: 99%
“…Electrophysiological measurements on oocytes and preimplantation embryos have shown that, like most somatic cells, oocytes and early embryos of mouse and human exhibit swelling-activated channel (VRAC or VSOAC) activity (Kolajova and Baltz, 1999;Hammer et al, 2000;Kolajova et al, 2001). In embryos, these channels have been shown to be permeable to a number of organic compounds, including osmolytes such as glycine and taurine (Kolajova and Baltz, 1999;Sonoda et al, 2003), and 1-cell mouse embryos can recover from cell swelling by activating these channels to release intracellular osmolytes including glycine (Seguin and Baltz, 1997;. Although the anion current presumably carried by VRAC in mouse embryos was downregulated during metaphase at the 2-to 4-cell transition, and remained low through the morula stage, swelling-activated efflux of organic osmolytes recovered after metaphase (Kolajova et al, 2001).…”
Section: Recovery From Cell Volume Increase and Release Of Accumulatementioning
confidence: 99%